Compressive sensing using directional filters for magnetic resonance image reconstruction under different k-space trajectories - Silva, Jessica Vivian Moreira da (2019)
Dissertação (Mestrado em Engenharia Biomédica). Universidade de Brasília, Brasília, 2019.